Saggi di Teoria della letteratura Percorsi tematici - Sabelli, Vincenzina (Moderna/Comparata, 2016)
In this book Saggi sulla teoria della letteratura ("Essays on the Theory of Literature") Enza Biagini puts in play her rich theoretical background and a vast knowledge of texts and authors to deal with some fundamental problems concerning literature, its status, its metamorphoses and its being necessary. Following modern paths, she leads the readers on the traces of different genres and situations difficult to define (the essay-writing, the unfinished ...), of 'temporary' themes always on the point of becoming something else (the nocturnal, the relationship between text and image. ..). The works revolve around the exergues and the definitions of the dictionaries: a whole world of suggestions and reasoning that the author finely brings not only to the field of theory, but also to the world of the Italian and French narrative.